Effect of cytochalasin D on Toxoplasma gondii cell entry. - Ryning, F W (1978)
Cytochalasin D did not prevent attachment but did prevent entry of Toxoplasma gondii into peritoneal macrophages and bladder tumor 4934 cells. Inhibition of entry of T. gondii into peritoneal macrophages by cytochalasin D was dose related and comparable to inhibition of phagocytosis. Prevention of entry of T. gondii into bladder tumor 4934 cells by cytochalasin D followed a dose response identical to that observed with peritoneal macrophages. After removal of the medium containing cytochalasin D, its effect was completely reversible, and the kinetics of the loss of inhibition followed a similar time course for both phagocytic and "nonphagocytic" cell types. The studies support the concept that the host cells actively participate in the process by which T. gondii gains entry into cells.